Dampak Sistem Informasi Akuntansi terhadap UMKM di Kawasan Asia: Tinjauan Literatur Sistematis - Wahyudi Nur Hidayat; Yusnaini Yusnaini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to assess the impact of Accounting Information Systems (AIS) on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Asia. To achieve this objective, this study uses a comprehensive literature review method. This study emphasizes how the implementation of AIS can improve management decision-making, operational efficiency, and financial reporting accuracy, considering the important role of MSMEs in the Asian economy. This study utilizes the PRISMA method and the Google Scholar database. 27 articles met the inclusion criteria. The results show that the implementation of AIS generally benefits the performance of MSMEs, although the impact varies depending on the sector, location, and scale of the business. It is evident that the success of AIS adoption is influenced by internal components, such as organizational culture, HR training, and management support, as well as external components, such as government policies and technological infrastructure. This study provides practical lessons for business actors and policy makers on how to create a more effective and inclusive MSME digitalization strategy in the Asian region. Keywords: Accounting Information Systems, MSMEs, Asia, Business Digitalization JEL Code: M41, L26, O32, C80